Analisis Pertimbangan Hakim dalam Pemberian Izin Dispensasi Kawin Di Bawah Umur di Pengadilan Agama Pandeglang - Nina Chairina; Sultan Isnansyah Fazri; Shinta, Shinta (Prodi Hukum Ekonomi Syariah (Muamalah), 2025)
This study investigates and answers questions about the reasons why the Pandeglang Religious Court grants underage marriage dispensation, as well as the positive and negative aspects of this regulation. The type of empirical legal research that is descriptive in nature is included in this study. Primary and secondary data are the main data of this study. Secondary data serves as a support for primary data. Data were collected through interviews and literature studies. Then, qualitative analysis and literature studies were used. Qualitative analysis is a method used by the author to see and study data stated by respondents verbally or in writing as well as their behavior directly. The purpose of this study was to determine the procedures, factors, and decisions of judges in handling applications for Marriage Dispensation. The results of this study are that the Procedure for submitting Marriage Dispensation at the Pandeglang Religious Court has been regulated in Perma no. 5 of 2019 systematically, the regulation was formed for the process of adjudicating Applications for Dispensation. In addition, several factors that cause the occurrence of Marriage Dispensation applications in Pandeglang The most important factor is the Religious Factor.